Experiences of ageism and digital technology use among older adults - Gudynaite, Gabriele; Zamalijeva, Olga; Pakalniskiene, Vilmante; Gegieckaite, Goda (Frontiers in Psychology, 2025)
ObjectiveDigital inclusion offers many opportunities to support well-being. However, the digital divide among older adults remains a significant barrier. While various technology-related factors have been identified, the impact of ageism on older adults’ use of digital technologies remains under-researched. This study aimed to analyze how older adults’ experiences of ageism relate to their use of digital technologies. It focused on internalized and relational ageism and explored confident and hesitant users’ experiences of ageism in relation to digital technology use.MethodsThe study employed a qualitative research strategy using focus group discussions. Thirteen older adults (4 males, 9 females), aged 65–82, participated in the study. Two focus group discussions were organized: the first consisted mostly of confident digital technology users (6 participants), and the second of mostly hesitant users (7 participants). Thematic analysis was employed, and the data were analyzed using ATLAS.ti (version 8).ResultsInternalized and relational ageism experiences were related to participants’ use of digital technologies. The potential multifaceted influence of internalized ageism on digital technology use was observed. Participants reported both subtle and overt forms of relational ageism, which related to their digital engagement in similarly negative ways. A potential interaction between relational and internalized ageism regarding participants’ use of digital technologies was observed. Confident and hesitant users differed in their experiences and responses to ageism. Confident users described social interactions as helping them resist ageist views, while hesitant users recalled interactions that reinforced stereotypes. Unexpectedly, a possible paradoxical impact of experiences of ageism was observed: for confident participants, it motivated digital technology use, whereas for hesitant users, it hindered it.ConclusionThe study demonstrated that ageism shapes older adults’ experiences with digital technologies and should be considered in future research on the digital divide. Further studies should replicate findings in other socio-cultural contexts, explore individual differences that explain why some older adults may be resilient to ageism while others more vulnerable. Additionally, research should continue to explore the broader impact of ageism across different areas of older adults’ lives.